The survival rate comparison of non small cell lung carcinoma patients who are given by epidermal growth factor receptor-tyrosin kinase inhibitor and those given by first-line chemotherapy treatment - Hasan Nyambe; Arif Santoso; Nur Ahmad Tabri; Harun Iskandar; Muh Ilyas; Edward Pandu Wiriyansyah (Faculty of Medicine, Hasanuddin University., 2021)
Introduction. Lung cancer is the type of non-small cell carcinoma (NSCLC) consists of non-squamous and squamous. Non-small cell lung cancer of non squamous types consist of adenocarcinoma and large cell carcinoma. Currently, lung cancer therapy is highly developed of chemotherapeutic agents to targeted therapy especially EGFR-TKI. This study aims to assess the survival rate of NSCLC patients who receive first line chemotherapy and those who recieve EGFR-TKI therapy at Wahidin Sudirohusodo hospital. Methods. This study is a retrospective study between 2017 to 2019 from the medical records of NSCLC patients who receive first-line chemotherapy and thise who recieve EGFR-TKI. Patients with platinum-based chemotherapy and EGFR-TKI with gefitinib therapy 1x250 mg/day or erlotinib 1x150mg/day and or afatinib 1x40 mg/day. Survival rate assessed from start to erect the diagnosis until the patient dies or when the study is discontinued. Result. From 239 subject of NSCLC patients consisted of 135 patients who receive first-line chemotherapy, and 104 patients are treate with EGFR-TKI. Based on the characteristics of the patients, most are more than 40 years old (chemotherapy 124 (91.9%) and EGFR-TKI 101 (97.1%) with the male gender that dominates (chemotherapy 98 (72.6%), EGFR-TKI 64 (61.5%). Smoking patients who received first-line chemotherapy are 65.2% and 61.5% of EGFR-TKIs with chemotherapy highest IB (severe IB 28.9%) and for EGFR-TKI (moderate IB are 26.9%). 73.2% of adenocarcinoma histology type with a predominance of stage IV 86.6% (83.7% for chemotherapy and EGFR-TKI 90.4%). Survival rate of patients are 98,7% for 6 months survival, 1 year survival rate is 94.1% and 2 years survival rate of 24.3%. Median survival patients who receiving EGFR-TKI longer than they received first- line chemotherapy (21 months versus 20 months). The 18 months PFS showed that patients treated with EGFR-TKI were 15 months, while patients receiving chemotherapy was 11 months. (P 0.000). Conclusion. Survival rates in NSCLC patients with EGFR-TKI therapy had significantly the highest survival rates compared with all other chemotherapy. Progression was faster in patients with first-line chemotherapy than EGFR-TKI. The factors that most influence the survival rate is type of therapy with p value<0.05.